Medical student satisfaction, coping and burnout in direct‐entry versus graduate‐entry programmes. Issue 6 (June 2016) - DeWitt, Dawn; Canny, Benedict J; Nitzberg, Michael; Choudri, Jennifer; Porter, Sarah
Abstract : Context: There is ongoing debate regarding the optimal length of medical training, with concern about the cost of prolonged training. Two simultaneous tracks currently exist in Australia: direct entry from high school and graduate entry for students with a bachelor degree. Medical schools are switching to graduate entry based on maturity, academic preparedness and career‐choice surety. We tested the assumption that graduate entry is better by exploring student preferences, coping, burnout, empathy and alcohol use. Methods: From a potential pool of 2188 participants, enrolled at five Australian medical schools, a convenience sample of 688 (31%) first and second year students completed a survey in the middle of the academic year. Participants answered questions about demographics, satisfaction and coping and completed three validated instruments. Results: Over 90% of students preferred their own entry‐type, though more graduate‐entry students were satisfied with their programme (82.4% versus 65.3%, p < 0.001). There was no difference between graduate‐entry and direct‐entry students in self‐reported coping or in the proportion of students meeting criteria for burnout (50.7% versus 51.2%). Direct‐entry students rated significantly higher for empathy (concern, p = 0.022; personal distress, p = 0.031). Graduate‐entry students reported significantly more alcohol use and hazardous drinking (30.0% versus 22.8%; p = 0.017). Conclusions: Our multi‐institution data confirm that students are generally satisfied with their choice of entry pathway and do not confirm significant psychosocial benefits of graduate entry. Overall, our data suggest that direct‐entry students cope with the workload and psychosocial challenges of medical school, in the first 2 years, as well as graduate‐entry students. Burnout and alcohol use should be addressed in both pathways. Despite studies showing similar academic outcomes, and higher total costs, more programmes in Australia are becoming graduate entry. Further research on non‐cognitive issues and outcomes is needed so that universities, government funders and the medical profession can decide whether graduate entry, direct entry, or a mix, is ideal. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.